2016
DOI: 10.1177/2333794x16663545
|View full text |Cite
|
Sign up to set email alerts
|

Global Health Simulation During Residency

Abstract: Resident participation in international health electives (IHEs) has been shown to be beneficial, yet not all residents have the opportunity to participate. We sought to determine whether participating in simulated global health cases, via the standardized Simulation Use for Global Away Rotations (SUGAR) curriculum, was useful for all pediatric residents, not merely those planning to go on an IHE. Pediatric residents in our program took part in 2 SUGAR cases and provided feedback via an online survey. Thirty-si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…7 These authors have demonstrated in multi-institutional studies that both residents traveling abroad and those staying within their institution find the curriculum useful for how to problem solve and reconcile the emotional challenges of working with limited-resources. 8,9 Since its introduction, the SUGAR curriculum has expanded to include SUGAR PEARLS (Procedural Education for Adaptation to Resource-Limited Settings)-a video training series on procedural adaptations-and has been implemented at over one hundred institutions across the world. 10 The SUGAR facilitator training is open-source and available online at sugarprep.org; however, its primary focus has been to train global health faculty on how to administer the curriculum.…”
Section: Introductionmentioning
confidence: 99%
“…7 These authors have demonstrated in multi-institutional studies that both residents traveling abroad and those staying within their institution find the curriculum useful for how to problem solve and reconcile the emotional challenges of working with limited-resources. 8,9 Since its introduction, the SUGAR curriculum has expanded to include SUGAR PEARLS (Procedural Education for Adaptation to Resource-Limited Settings)-a video training series on procedural adaptations-and has been implemented at over one hundred institutions across the world. 10 The SUGAR facilitator training is open-source and available online at sugarprep.org; however, its primary focus has been to train global health faculty on how to administer the curriculum.…”
Section: Introductionmentioning
confidence: 99%
“…6 The Midwest Consortium has created several highquality open-access curricula in global health education, including simulation cases, an online video series for procedural adaptations, and a comprehensive predeparture preparation curriculum, all described in previous publications and freely available online. [6][7][8][9][10] These have been widely disseminated to over 200 institutions in over 20 countries via the online platform, sugarprep.org.…”
mentioning
confidence: 99%